Clinical outcomes of locking polymeric clip for laparoscopic appendectomy in patients with appendicitis: a retrospective comparison with loop ligature - Seokwon Kim; Byong Ho Jeon; Sang Sik Cho; Ui Sup Shin; Sun Mi Moon (Annals of Coloproctology, 2022)
Purpose This study aimed to compare the clinical outcomes of laparoscopic appendectomy (LA) according to the method of appendiceal stump closure. Methods Patients who underwent LA for appendicitis between 2010 and 2020 were retrospectively reviewed. Patients were classified into locking polymeric clip (LPC) and loop ligature (LL) groups. Clinical outcomes were compared between the groups. Results LPC and LL were used in 188 (56.6%) and 144 patients (43.4%), respectively for appendiceal stump closure. No significant differences were observed in sex, age, comorbidities, and the severity of appendicitis between the groups. The median operative time was shorter in the LPC group than in the LL group (64.5 minutes vs. 71.5 minutes, P=0.027). The median hospital stay was longer in the LL group than in the LPC group (4 days vs. 3 days, P=0.020). Postoperative incidences of intraabdominal abscess and ileus were higher in the LL group than in the LPC group (4.2% vs. 1.1%, P=0.082 and 2.8% vs. 0%, P=0.035; respectively). The readmission rate was higher in the LL group than that in the LPC group (6.3% vs. 1.1%, P=0.012). Conclusion Using LPC for appendiceal stump closure during LA for appendicitis was associated with lower postoperative complication rate, shorter operative time, and shorter hospital stay compared to the use of LL. Operative time above 60 minutes and the use of LL were identified as independent risk factors for postoperative complications in LA. Therefore, LPC could be considered a more favorable closure method than LL during LA for appendicitis.